PEMBANGUNAN INFRASTRUKTUR FIBER TO THE HOME OLEH PT IKHLAS CIPTA TEKNOLOGI DI KAWASAN DESA JATIRANGGON - Dikky Setiyanto; Apriade Voutama (Jurnal Ilmiah Matrik, 2023)
In the current era of globalization, the world of technology and information, especially the computer world, is developing very rapidly. Fiber to the Home (FTTH) is one example of the results of the development of the Internet. Fiber to the Home (FTTH) is a fiber-optic-based network communication device that provides various services such as the Internet, telephone network as well as live television broadcasts to private users. Today, many people need the Internet for many activities that require an Internet connection. When we build a FTTH (Fiber to the Home) network, we must build a quality network that is not only connected to the Internet, especially now that many ISPs are building FTTH (Fiber to the Home) networks requiring innovation. In this research, we tested the quality of the Internet, by testing the Quality of Services, which took into account download speed, upload speed, latency, delay and packet loss. The results of the test show that the download speed is 66.22Mbps, upload is 73.69Mbps, ping latency is around 5-8ms, and jitter is 7.84